Advocate - Jones, Rachel Leah; Bellaiche, Philippe (Israel ; Canada ; Switzerland : Cinephil, 2019)
Advocate follows the caseload of human rights lawyer Lea Tsemel in real time, including the high-profile trial of a 13-year-old boy, her youngest client to date. The film also revisits her landmark cases and reflects on the political significance of her work, as well as the personal price she pays for taking on the role of “devil’s advocate”.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films